Réponses

2012-10-20T21:42:15+02:00

bonsoir

factoriser

F = (5x-3)(3x+2) - (5x-3)²

F = (5x-3)(3x+2) - (5x-3)(5x-3) 

F = (5x-3) ( 3x+2-5x+3 ) 

F = (5x-3)(-2x+5)

développer

F = -10x² +25x+6x -15

F = -10x² +31x - 15 

2012-10-20T22:58:05+02:00

Coucou ! Les etoiles * , c'est le signe fois X . 

Pour factoriser : 

F = (5x-3)(3x+2) - (5x-3)²

F = (5x-3)(3x+2) - (5x-3)(5x-3) 

F = (5x-3) ( 3x+2-5x+3 ) 

F = (5x-3)(-2x+5)

 

Pour développer :

F = (5x-3)(3x+2) - (5x-3)²
F = (5x*3x + 5x*2 - 3*3x - 3*2) - (5x² - 2*5x*3 + 3²) 
F =  (15x² + 10x - 9x - 6 ) - ( 5x² - 30x + 9) 
F = 15x² + 1x - 6 - 5x² + 30x - 9 .

F = 10x² + 31x - 15.